Birth defects data from population‐based birth defects surveillance programs in the United States, 2007 to 2011: Highlighting orofacial clefts. Issue 11 (14th November 2014) - Mai, Cara T.; Cassell, Cynthia H.; Meyer, Robert E.; Isenburg, Jennifer; Canfield, Mark A.; Rickard, Russel; Olney, Richard S.; Stallings, Erin B.; Beck, Meredith; Hashmi, S. Shahrukh; Cho, Sook Ja; Kirby, Russell S.; et al.
<x xml:space="preserve">Abstract</x> © 2014 The Authors Birth Defects Research Part A: Clinical and Molecular Teratology Published by Wiley Periodicals, Inc.